Molecular mechanisms of low dose ionizing radiation-induced hormesis, adaptive responses, radioresistance, bystander effects, and genomic instability. (January 2015) - Tang, Feng Ru; Loke, Weng Keong
Abstract Purposes: To review research progress on the molecular mechanisms of low dose ionizing radiation (LDIR)-induced hormesis, adaptive responses, radioresistance, bystander effects, and genomic instability in order to provide clues for therapeutic approaches to enhance biopositive effects (defined as radiation-induced beneficial effects to the organism), and control bionegative effects (defined as radiation-induced harmful effects to the organism) and related human diseases. Conclusions: Experimental studies have indicated that Ataxia telangiectasia-mutated (ATM), extracellular signal-related kinase (ERK), mitogen-activated protein kinase (MAPK), phospho-c-Jun NH2-terminal kinase (JNK) and protein 53 (P53)-related signal transduction pathways may be involved in LDIR-induced hormesis; MAPK, P53 may be important for adaptive response; ATM, cyclooxygenase-2 (COX-2), ERK, JNK, reactive oxygen species (ROS), P53 for radioresistance; COX-2, ERK, MAPK, ROS, tumor necrosis factor receptor alpha (TNFα) for LDIR-induced bystander effect; whereas ATM, ERK, MAPK, P53, ROS, TNFα-related signal transduction pathways are involved in LDIR-induced genomic instability. These results suggest that different manifestations of LDIR-induced cellular responses may have different signal transduction pathways. On the other hand, LDIR-induced different responses may also share the same signal transduction pathways. For instance, P53 has been involved in LDIR-induced hormesis, adaptive response, radioresistance and genomic instability. Current data therefore suggest that caution should be taken when designing therapeutic approaches using LDIR to induce beneficial effects in humans.